Word-forming Potential of Prefixes де- and ре- in the Current Political Situation (Based on the Material of the Media and Internet) - Sofia Sergeevna Stavitskaya (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This article analyses prefixed nonce and potential words with prefixes де- and ре-. The choice of material, i.e. potential and nonce words with prefixes де- and ре-, is due to the high frequency of using lexemes with these prefixes in the modern news agenda. The purpose of this study is to assess the word-forming potential of prefixes in modern political contexts of the media and the internet by describing their word-forming compatibility with verbs and nouns, as well as identify the new words as nonce or potential ones according to the highlighted criteria, which are correspondence of prefixal lexemes to word-forming models (or vice versa, violation of productive models) of the Russian language and the degree of connection of the word with the context that caused it to appear. The work demonstrates the productivity of lexemes with prefixes of де- and ре- in the sociopolitical contexts of the media and the internet using the example of the work of previous researchers over the past decades. As additional criteria, the euphony of the new formation, the presence or absence of elements of word play, expressiveness and the presence of authorial connotations are considered. The work uses methods of contextual and word-formation analyses. The author of the study relies on fundamental works on Russian word formation. Based on the results of the study, the ratio of new potential and nonce words with the studied prefixes within the studied contexts is established and a conclusion is drawn about the high productivity of the де- and ре- prefixes not only in creating neologisms as new words reflecting the linguistic need to close speech lacunae, but also connected to the context of authorial nonce words, no less representative from the point of view of studying prefixal valence due to their expressiveness.